Elamipretide Attenuates Pyroptosis and Perioperative Neurocognitive Disorders in Aged Mice - Zuo, Youmei; Yin, Lei; Cheng, Xinqi; Li, Jun; Wu, Hao; Liu, Xuesheng; Gu, Erwei; Wu, Jing (Frontiers in Cellular Neuroscience, 2020)
Pyroptosis is a recently characterized inflammatory form of programmed cell death that is thought to be involved in the pathogenesis of perioperative neurocognitive disorders (PND). Elamipretide (SS-31), a mitochondrial-targeted peptide with multiple pharmacological properties, including anti-inflammatory activity, has been demonstrated to protect against many neurological diseases. However, the effect of elamipretide on pyroptosis in PND has not been studied. We established an animal model of PND by performing an exploratory laparotomy on mice under isoflurane anesthesia and examined the effects of elamipretide on cognitive function, synaptic integrity, neuroinflammation, mitochondrial function, and signaling controlling pyroptosis. Our results showed that anesthesia and surgery caused mitochondrial dysfunction and abnormal morphology, activation of NLRP3 inflammasome-caspase-1 dependent pyroptosis, and downregulation of synaptic integrity-related proteins in the hippocampus in aged mice, thus leading to learning and memory deficits in behavioral tests. Remarkably, treatment with the mitochondrial-targeted peptide elamipretide not only had protective effects against mitochondrial dysfunction but also attenuated surgery-induced pyroptosis and cognitive deficits. Our results provide a promising strategy for the treatment of PND involving mitochondrial dysfunction and pyroptosis.